EXPERIMENTAL ASSESSMENT OF FLEXURAL PERFORMANCE IN CONCRETE BEAMS REINFORCED WITH ANGLE STEEL PROFILES: A COMPARATIVE STUDY AGAINST TYPICAL REINFORCEMENT SYSTEMS - Pratiwi, Ade Yuniati; Afriyono, Hari; Chairunnisa, Nursiah; Krasna, Wiku Adhiwicaksana; Nurwidayati, Ratni; Fahreza, Ahmad (Journal of Applied Engineering Science, 2025)
This study investigates the performance of modified reinforced concrete (RC) beams with truss systems, specifically Pratt-truss and Warren-truss, compared to typical reinforcement systems through flexural strength tests. Aiming to enhance load-carrying capacity, the use of angle steel profiles in the truss systems to transform standard reinforcement bars was analyzed. The flexural strength evaluation involved eight specimens: two with conventional reinforcement, three with Pratt-truss, and three with Warren-truss, each measuring 15 x 15 x 120 cm. The focus was on initial stiffness, secant stiffness, and ductility. Results showed a notable performance increase with truss systems: a 7.5% rise in average initial stiffness, a 1.2% improvement in secant stiffness, and a 5.7% enhancement in displacement ductility, highlighting their potential for safer and more durable structures. The Pratt truss system exhibited the highest ductility, followed by the Warren truss and the standard system. Experimental observations indicated that the typical reinforcement system initially showed flexural cracks at the bottom of the beam, later followed by diagonal shear cracks, which intensified under load, causing concrete to crush in the compression zone. A similar pattern was observed in truss-reinforced beams, with initial flexural cracks at the beam’s bottom progressing under load, ultimately resulting in concrete crushing in the same area. Crack propagation in both systems involved the formation and expansion of cracks along the diagonal and vertical framework, indicating flexural cracks.